Tense in Proto-Bantu - Nurse, Derek; Watters, John (My University, 2022)
The focus of this chapter is the appearance of tense in Proto-Bantu (PB). Most Niger-Congo (NC) languages are aspect-prominent, having no tense contrasts, and the same is generally assumed for ancestral Proto-Niger-Congo. PB emerged from part of an eastern subgroup of NC to which we refer as Bantoid. Some 5000 years ago or earlier, tense was innovated at an early stage in a region along and to the east of the Cameroon Volcanic Line. This means that tense is not unique to PB but is inherited by PB from its forebears. We propose two lines of verbal development for Narrow Bantu (NB) based on the verbal phenomena we traced. The data did not always allow us to base our analysis on the strict application of the Comparative Method to the exponents of tense and aspect, but examination of specific systematic features of the verbal systems in NB and parts of Bantoid led us to infer plausible paths of verbal development to explain the data.
Keywords: Tense; Proto-Bantu; Verbal Development